Pain level between clear aligners and fixed appliances: a systematic review - Paula Coutinho Cardoso; Daybelis Gonzalez Espinosa; Paulo Mecenas; Carlos Flores-Mir; David Normando (SpringerOpen, 2020)
Abstract Objectives To assess if there is any difference in pain levels between orthodontic treatment with clear aligners or fixed appliances. Materials and methods An electronic search was completed in PubMed, The Cochrane Database, Web of Science, Scopus, Lilacs, Google Scholar, Clinical Trials, and OpenGrey databases without any restrictions until February 2019. All comparative study types contrasting pain levels between clear aligners and fixed appliances were included. The risk of bias (RoB) was assessed using the Newcastle-Ottawa Scale, ROBINS-I-Tool, or ROB 2.0 according to the study design. The level of evidence was assessed through the GRADE tool. Results After removal of duplicates, exclusion by title and abstract, and reading the full text, only seven articles were included. Five were prospective non-randomized clinical trials (CCT), one was a cross-sectional study, and one was a randomized clinical trial (RCT). Two studies presented a high RoB, three a moderate RoB, and two a low RoB (including the RCT). A meta-analysis was not performed because of clinical, statistical, and methodological heterogeneity. Most of the studies found that pain levels in patients treated with Invisalign were lower than those treated with conventional fixed appliances during the first days of treatment. Differences disappeared thereafter. No evidence was identified for other brands of clear aligners. Conclusions Based on a moderate level of certainty, orthodontic patients treated with Invisalign appear to feel lower levels of pain than those treated with fixed appliances during the first few days of treatment. Thereafter (up to 3 months), differences were not noted. Malocclusion complexity level among included studies was mild. Pain is one of many considerations and predictability and technical outcome are more important, mainly considering that the difference does not seem to occur after the first months of the orthodontic treatment.